Evaluation of Physical Disabilities in People with Leprosy Employing Two Indicators: Degree of Physical Disability Indicator and The Eyes-Hands-Feet Score - Nardi, Susilene Maria Toneli (2011)
The aim of this study was to assess and compare the degree of physical disability of the eyes, hands and feet between the clinical forms of leprosy at diagnosis and at the end of treatment based on the “World Health Organization Degree of Physical Disability Indicator”(GPD-WHO) and the Eyes-Hands-Feet score (EHF). This was a retrospective cross-sectional descriptive study. The medical records of 384 individuals diagnosed with leprosy from 1994 to 2006 were revisited using a protocol designed for this study. The mean age of the patients was 51.7 years and 62.8% of patients had multibacillary leprosy with a predominance oftheboderline form (40.4%). Of the cases evaluated, 33.2% and 25.9% presented some type of disability atdiagnosis and at completion of multidrug treatment, respectively. Individuals with the lepromatous formpresented with the most disabilities (47% at diagnosis and 39.4% at completion of treatment) and the legswere the most affected part of the body (18.2%). Improvements in disabilities were seen in most clinicalforms (p-value < 0.05). According to the two indicators, the clinical status remained unchanged in 76.3% ofcases, improved in 8.2% and worsened in 15.5%. An analysis of disabilities using the DPD-WHO and the EHFgives a more sensitive and critical assessment of the status of affected segments in leprosy. On comparingthe disabilities outlined at diagnosis and at completion of treatment, there was a significant improvementin most clinical forms; the legs are the most affected region in leprosy.